2021
DOI: 10.2147/dmso.s297315
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-Related Distress Among People with Type 2 Diabetes in Ho Chi Minh City, Vietnam: Prevalence and Associated Factors

Abstract: Background Diabetes-related distress (DRD) refers to the condition of negative emotion as a result of living with diabetes and the burden of self-care. This study aims to evaluate the prevalence and associated factors of DRD among people with type 2 diabetes. Methods A cross-sectional study was carried out on people with Type 2 Diabetes at three hospitals in Ho Chi Minh City, between April and November 2020. The study used the Vietnamese version of the Diabetes Distress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
10
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 22 publications
7
10
2
2
Order By: Relevance
“…Similar to Huynh et al, we observed no influence of gender on the risk of DD [ 24 ]. However, few studies have reported that women are at higher risk of DD [ 2 , 3 , 9 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar to Huynh et al, we observed no influence of gender on the risk of DD [ 24 ]. However, few studies have reported that women are at higher risk of DD [ 2 , 3 , 9 ].…”
Section: Discussionsupporting
confidence: 90%
“…Emotional burden (68.7%) and regimen-related distress (66%) were more important domains than interpersonal distress (37.7%) and physician-related distress (28.6%) in measuring DD. Similar observations were found in another context [ 9 , 22 , 24 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Diabetic depression is also related to genetic (family background history) and social factors to diabetes distress, which present the burden of disease and its treatment [16,17]. Recent studies have found that most diabetic patients with elevated depression are not clinically ill but suffer from diabetes-related distress [9,10,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…7 Female gender and depression were the only factors identified in the meta-analysis of Perrin et al as being associated with DRD, but a plethora of other factors emerged from the literature such as age, body mass index (BMI), glycemic control, duration of diabetes, lifestyle habits, treatment regimens, level of education etc. 7,[10][11][12][13][14][15][16] DRD has important health-related consequences such as worse glycemic outcomes, poorer medication adherence and diabetes self-care, and poorer quality of life. 5,17 A recent study reported that in patients with T2DM, depressive symptoms were associated with lower self-management behavior and higher glycated hemoglobin (HbA1c), while DRD was associated with higher HbA1c, suggesting that patients with both depression and DRD might have worse outcomes.…”
mentioning
confidence: 99%